2014
DOI: 10.1002/hed.23562
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of central node necrosis in predicting extracapsular spread among oral cavity squamous cell carcinoma

Abstract: Our findings suggest that central node necrosis on preoperative CT scans is strongly associated with the presence of ECS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
5
19
0
Order By: Relevance
“…Cervical nodal metastasis is very common and has a substantial effect on prognosis in patients with HNSCC. Zoumalan et al (13) and Randall et al (14) reported that CNN that was visible at preoperative CT was a useful indicator of extracapsular nodal spread, which was confirmed to be an important negative prognostic indicator in patients with HNSCC, with a sensitivity of 91%-95% and a negative predictive value of 88%-98% (15)(16)(17)(18)(19). These previous studies indirectly suggested that CNN may also be a negative prognostic factor in patients with HNSCC, including NPC; the results of our current study confirm this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical nodal metastasis is very common and has a substantial effect on prognosis in patients with HNSCC. Zoumalan et al (13) and Randall et al (14) reported that CNN that was visible at preoperative CT was a useful indicator of extracapsular nodal spread, which was confirmed to be an important negative prognostic indicator in patients with HNSCC, with a sensitivity of 91%-95% and a negative predictive value of 88%-98% (15)(16)(17)(18)(19). These previous studies indirectly suggested that CNN may also be a negative prognostic factor in patients with HNSCC, including NPC; the results of our current study confirm this suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that rates of distant metastasis were higher in npc patients with retropharyngeal lymph node involvement. Zoumalan et al 14 and Randall et al 15 reported that cervical node necrosis visible on preoperative ct was a useful indicator of extracapsular nodal spread, which was confirmed to be an important negative prognostic indicator in patients with head-and-neck squamous cell carcinoma, with a sensitivity of 91%-95% and a negative predictive value of 88%-98% [16][17][18][19] . Those studies appear to suggest that snn might also be an unfavourable prognostic factor in patients with npc, and the results of the present study confirmed that suggestion.…”
Section: Discussionmentioning
confidence: 97%
“…Lymph node central necrosis, viewed by CT preoperatively, was noted to be an indicator for extracapsular spread, while lymph node diameter was not influential 27,28. However, a study by King et al17 showed that MRI was at par with CT in the detection of CNN with similar diagnostic accuracies and sensitivities (MRI: 91%–99% accuracy and 93% sensitivity; CT: 92%–99% accuracy and 91% sensitivity).…”
Section: Discussionmentioning
confidence: 99%